2016
DOI: 10.1111/twec.12427
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Rules and Twin Deficits: The Link between Fiscal and External Balances

Abstract: This paper investigates the relationship between countries' fiscal balances and current accounts with an emphasis on the role of fiscal rules. The direct effect of fiscal policy on the current account via aggregate (import) demand is potentially amplified by indirect effects, materialising through interest rate effects and intergenerational transfers that reduce savings. On the other hand, the implied positive relation between fiscal and external balances is potentially attenuated by offsetting changes in savi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…We further applied Granger causality test the results concluded that there is a strong inverse causal relationship between budget deficit and current account deficit meaning that Keynesian preposition is more plausible than Ricardian Equivalence theorem in the light of above data. Our results are consistent with Banday and Aneja, (2019); Banday and Aneja, (2016); Ganchev, 2010; Bhat and Sharma (2018); Badinger et al (2017), and Afonso et al (2018).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We further applied Granger causality test the results concluded that there is a strong inverse causal relationship between budget deficit and current account deficit meaning that Keynesian preposition is more plausible than Ricardian Equivalence theorem in the light of above data. Our results are consistent with Banday and Aneja, (2019); Banday and Aneja, (2016); Ganchev, 2010; Bhat and Sharma (2018); Badinger et al (2017), and Afonso et al (2018).…”
Section: Resultssupporting
confidence: 92%
“…Garg and Prabheesh (2017) investigate the twin deficit for India by using ARDL model and confirm the twin deficit hypothesis. Badinger et al (2017) investigated the role of fiscal rules in the relationship between fiscal and external balances for 73 countries over the period of 1985-2012. Their results confirm the twin deficits hypothesis.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…4 In theory, in the case of perfect capital mobility, with capital flowing among countries to equalise the yield to investors, the current account deficit could increase by exactly the same amount as the budget deficit. 5 On the other hand, while a fiscal expansion can drive the current account into deficit, the resulting eventual higher interest rates can push the capital account into surplus. Therefore, the final effect on foreign reserves accumulation is less clear, and depends on the relative sensitivity of international capital flows and on the responsiveness of imports to income.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Dornbusch (1976) showed that the interest rate is a key factor between the adjustments of the domestic economy and of the current account 5. With perfect capital mobility, fiscal policy cannot restore the internal balance(Mundell, 1963).…”
mentioning
confidence: 99%
“…The same holds true for GDP growth, but a difference might arise in the trade balance of capital goods, which can deteriorate with higher GDP growth rates in a different manner than the consumer goods’ balance, especially if GDP growth is more export driven. While the related literature has mostly found positive relationships between fiscal and external balances (see, e.g., Badinger, Fichet de Clairfontaine, & Reuter, ; for recent empirical evidence), the effects of fiscal expansion on trade balances can vary across product categories, depending on the composition of government spending, for example whether it spends relatively more on capital than on consumer goods. There might also be differences in tastes or in consumption and saving patterns depending on the relative development level of single countries, which is why we control for real GDP per capita in one of our specifications.…”
Section: Data Developments and Empirical Approachmentioning
confidence: 99%